Removal of phosphorus from aqueous solutions by granular mesoporous ceramic adsorbent based on Hangjin clay. Issue 47 (7th October 2016) - Wang, Di; Hu, Weiwu; Chen, Nan; Yu, Yang; Tian, Caixing; Feng, Chuanping
Abstract: A new granular mesoporous ceramic adsorbent based on Hangjin clay was developed to evaluate the feasibility for phosphorus removal from aqueous environment. Batch experiments were performed to study the influence of various experimental parameters such as contact time, initial phosphorus concentration, initial pH, and surrounding temperature on the adsorption of phosphorus. Four kinetic models were tested, and the pseudo-second-order kinetic model fitted well with the adsorption kinetics. Besides that, the kinetic data were also fitted to the intra-particle diffusion model, presenting three linear regions, indicating that the kinetics of adsorption should follow multiple sorption rates. The equilibrium data revealed the Sips and Redlich–Peterson isotherm models fitted well with the phosphorus sorption process. The maximum adsorption capacity of ceramic adsorbent for phosphorus removal was 5.96 mg g −1 . The optimum phosphorus removal was observed between pH ranges of 4.0–12.0. The calculated thermodynamic parameters indicated that the adsorption process was spontaneous and endothermic in nature. Adsorption process appeared to be controlled by the mechanism of electrostatic attraction, ligand exchange, and chemical precipitation.